Social Media and Their Potential in Generating Value in Organizations - Łaszkiewicz, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The article presents the issues of social media and their potential use in organizations in order to generate value for employees, customers and investors. In addition to value definitions, which is now regarded as one of the main determinants of achieving a competitive advantage in the market, the author discusses the concept of social media. Author also describes distinguish features of the Social Era that create potentially new areas of value creation and discusses the role of the client in this process.